Dependence of ski jump length on the skier's body pose at the beginning of take-off - Zanevskyy, I.; Banakh, V. (Acta of Bioengineering and Biomechanics, 2010)
This paper deals with the way of using the device for three-dimensional motion analysis allowing the interaction between the movable segments of the hand to be described. The aims of this study were to investigate the angular patterns of the MCP joints for the fingers I-V during the grip of four commonly used objects and to compare the results between the dominant/non-dominant hands and in both male and female groups. The experiment was carried on 48 right-handed subjects (24 males and 24 females) selected at random, aged between 20 and 23. The 3-D motion capture system, that was used, consisted of 5 strobe cameras and a hand model consisting of 15 kinematic pairs with the total mobility of 20 degrees of freedom. In this study, mean, standard deviation, median, minimum, maximum and the ranges of flexion/extension and radial/ulnar deviation were separately described for each finger MCP joint. For statistical analysis and in search for the variability of angular parameters of MCP joints during a grip, the Mann-Whitney U test was used.